Development of the mental health cultural adaptation and contextualization for implementation (mhCACI) procedure: a systematic framework to prepare evidence-based psychological interventions for scaling. (19th February 2021) - Sangraula, Manaswi; Kohrt, Brandon A.; Ghimire, Renasha; Shrestha, Pragya; Luitel, Nagendra P.; van't Hof, Edith; Dawson, Katie; Jordans, Mark J. D.
Abstract: Background: Because of the high burden of untreated mental illness in humanitarian settings and low- and middle-income countries, scaling-up effective psychological interventions require a cultural adaptation process that is feasible and acceptable. Our adaptation process incorporates changes into both content and implementation strategies, with a focus on local understandings of distress and treatment mechanisms of action. Methods: Building upon the ecological validity model, we developed a 10-step process, the mental health Cultural Adaptation and Contextualization for Implementation (mhCACI) procedure, and piloted this approach in Nepal for Group Problem Management Plus (PM+), a task-sharing intervention, proven effective for adults with psychological distress in low-resource settings. Detailed documentation tools were used to ensure rigor and transparency during the adaptation process. Findings: The mhCACI is a 10-step process: (1) identify mechanisms of action, (2) conduct a literature desk review for the culture and context, (3) conduct a training-of-trainers, (4) translate intervention materials, (5) conduct an expert read-through of the materials, (6) qualitative assessment of intervention population and site, (7) conduct practice rounds, (8) conduct an adaptation workshop with experts and implementers, (9) pilot test the training, supervision, and implementation, and (10) review through process evaluation. For Group PM+, key adaptations were harmonizing the mechanisms of action with cultural models of 'tension'; modification of recruitment procedures to assure fit; and development of a skills checklist. Conclusion: A 10-step mhCACI process could feasibly be implemented in a humanitarian setting to rapidly prepare a psychological intervention for widespread implementation.